From the legal issues of financing official controls of foodstuffs - Serlikowska, Agnieszka (Przegląd Prawa Rolnego, 2018)
The purpose of these deliberations is an attempt to answer the question of whether the legal instruments concerning the financing of statutory food controls ensure proper functioning of this form of supervision. In particular, the functioning of the system of fees in various EU Member States has been analysed. It has been found out that despite the fact that the EU legislator has regulated the system of financing official controls of foodstuffs, most national regulations do not provide sufficiently for the proper functioning of the control system, and do not ensure that all costs incurred are recovered. Moreover, the unclear criteria according to which the financing system operates reduces confidence in public administration bodies.